Blunt traumatic coronary artery dissection: A case study. (February 2022) - Blevins, Aaron J.; Repas, Steven J.; Alexander, Brittney M.; Siebenburgen, Christa
Abstract: Background: Coronary artery dissection is an extremely rare but lethal complication of blunt chest trauma. Dissection may cause thrombus formation or vasospasm, leading to the clinical presentation of acute myocardial infarction. Diagnosis can be difficult as traumatic chest pain has several etiologies; therefore, an electrocardiogram (ECG) is necessary in all cases of thoracic trauma [1-3]. Case report: Thirty-eight-year old female, with no significant past medical history, presented to a freestanding emergency department with complaints of severe chest pain and right shoulder pain after a blunt trauma water sport accident. Upon selective angiography of left and right coronary artery and left heart catheterization, the patient was found to have an occluded distal left anterior descending artery (LAD). The patient underwent aspiration thrombectomy of the proximal LAD artery and percutaneous transluminal coronary angioplasty (PTCA) of distal LAD artery, which decreased the stenosis from 100% to less than 10%. The patient was discharged home on hospital day three with follow up in one month. Coronary artery dissection should be considered in blunt thoracic trauma particularly in cases of unexplained chest pain, regardless of the mechanism of injury, age of patient or comorbidities. Patients should be evaluated with an ECG, troponin, and possibly an echocardiogram to rule out this type of injury.